1992
DOI: 10.1021/jf00016a014
|View full text |Cite
|
Sign up to set email alerts
|

Volatile constituents of green and ripened pineapple (Ananas comosus [L.] Merr.)

Abstract: Volatile constituents of green and ripened pineapples were isolated and identified by gas chromatography and gas chromatography/mass spectrometry. The numbers of volatiles found were 144 and 127 in green and ripened pineapples, respectively. Among a total of 157 constituents identified, 50 were identified for the first time from pineapple. Esters constituted over 80% of total volatiles from both green and ripened pineapples. The major volatile constituents in green pineapples were ethyl acetate and ethyl 3-(me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
100
0
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 5 publications
9
100
0
5
Order By: Relevance
“…It would seem that the sensor array is comprised of sensors able to detect the different volatile compounds released from pineapple at different storage times. Volatile compounds cited above were reported as pineapple aroma constituents by researchers in the past (Engel et al, 1990;Umano et al, 1992;Elss et al, 2005). The ability of the electronic nose in discriminating samples as function of the storage temperature confirmed results obtained previously for fish , meat (Limbo et al, 2010) and cheese (Benedetti et al, 2005).…”
Section: Discontinuous Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…It would seem that the sensor array is comprised of sensors able to detect the different volatile compounds released from pineapple at different storage times. Volatile compounds cited above were reported as pineapple aroma constituents by researchers in the past (Engel et al, 1990;Umano et al, 1992;Elss et al, 2005). The ability of the electronic nose in discriminating samples as function of the storage temperature confirmed results obtained previously for fish , meat (Limbo et al, 2010) and cheese (Benedetti et al, 2005).…”
Section: Discontinuous Methodssupporting
confidence: 73%
“…In contrast, the other sensors were characterized by an increasing trend. These sensors are most likely sensitive to volatile compounds related to the pineapple microflora metabolism or to the aerobic activity of the fruit product (Umano et al, 1992), and are responsible for the ethanol, ethylene and off-flavour development during storage (Spanier et al, 1998;Marrero and Kader, 2006;Montero-Calderón et al, 2008). The same qualitative trends were observed for the sample stored at 7.6 and 16.0 • C (data not shown).…”
Section: Continuous Methodsmentioning
confidence: 52%
“…The fact that its concentration is most often under its individual olfactory threshold implies an indirect impact [ 5 ], further described as hyper additive because its addition decreased the threshold of the total aromatic reconstitution by 2.09 fold, although it did not affect the aroma perceived [ 15 ]. Other compounds of the same family, such as ethyl 2 hydroxy 2 methylbutanoate, have been identified in Tokaji wines [ 16 ] and pineapple [ 17 ], while ethyl 3 hydroxy 3 methylbutanoate has been found in cashew apple juice [ 18 ] and other fruits [ 19 -21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Terpens were also the main group of aroma volatile compounds, and T2 had the highest content. Previous researchers had reported that terpenes were also the main volatiles in the fruits of pineapple [21,22].…”
Section: Effect Of B On Aroma Volatile Compounds Of Pineapple Fruitmentioning
confidence: 97%